Determination of skin penetration profiles by confocal Raman microspectroscopy: Evaluation of interindividual variability and interlab comparability - Binder, Lisa; Valenta, Claudia; Lunter, Dominique (Journal of Raman spectroscopy, 2020)
Confocal Raman microspectroscopy is being increasingly used to investigate the skin penetration of actives and excipients. The aim of the present study was to compare results obtained with skin from different donors, acquired with two Raman systems: the RiverD gen2 Skin Composition Analyzer and the WiTec alpha 500 instrument. To elucidate the interindividual variability between the skin donors and to find out whether the two systems would give similar results in skin penetration analysis, we compared the penetration of the model drug procaine from hydrogel formulations with or without the penetration enhancer POE‐23‐lauryl ether. Penetration was investigated with both systems on skin from three different skin donors, each. Penetration plots were prepared by plotting the signal intensity of a typical peak of procaine against the skin depth. We then calculated the enhancement ratio from the areas under the curves of the penetration plots of procaine that had penetrated from the formulation with or without the enhancer. They ranged between 2.0 and 3.1 for the WiTec system and between 2.1 and 3.1 for the RiverD system. Thus, we found that both systems provide similar estimations of the skin penetration of procaine. Results of skin penetration analysis by two commonly used confocal Raman microspectroscopy systems was found to be comparable between two laboratories.